La participación ciudadana en la gestión del Gobierno Autónomo Descentralizado del Cantón Chone en el periodo 2011 -2015. - Córdova Zambrano, Katherine Isabel (2017)
The purpose of this research was to analyze citizen participation in the management of the Decentralized Autonomous Government of Canton Chone, to determine its incidence during the period 2011-2015, in the execution of this study was used the methods of deductive, inductive and Descriptive, in addition a field visit was made to know the current situation of the institution, bibliographical information on the subject was collected, an observation sheet was applied through indicators that established the level of citizen participation, the interview to the mayor based the investigation, And the survey of social actors allowed to know the incidence of the mechanisms of citizen participation in the development of the canton Chone, it can be concluded that the regulatory policies are based on Article 100 of the Constitution of the Republic that stipulates that instances Of participation, composed of elected officials, representatives of the dependent regime and society at each level of government, it was determined that the mechanisms that are applied are the veedurías, the empty chair, cantonal assemblies, these are developed with the social actors that are The cantonal leaders, in this way is achieved that are complied with the works proposed by this public institution.